Characteristics of abortus patients in Dr. Soetomo Hospital, Surabaya, Indonesia - Kadek Novita Damayanti; Muhammad Yusuf; Sudarno Sudarno (Majalah Obstetri dan Ginekologi, 2020)
Objective: The purpose is to uncover the characteristics of abortion patients in Dr. Soetomo general hospital in 2014.Materials and Methods: This study has analized with descriptive observational method using data from medic records on patient that fulfilled inclusion criterias in Dr. Soetomo general hospital during the periods of January 1st - December 31st 2014. Researcher used various variables such as patient’s age, gestational age, parity, previous history of abortion, previous history of contraception and type of abortion. From 40 patients, only 31 patients that fulfilled those inclusion criteria.Results: This study found that from 31 patients of abortion, the age group is dominated by more than 35 years old (52%). Most gestational age of abortion’s patients comes before 20 weeks (68%). Parity occurance is dominated by multiparity (39%). Most of them have no previous history of abortion (55%). Most of them also have no previous history of contraception (65%). And the type of abortion is dominated by Threatened Abortion (61%).Conclusion: Characteristics of abortion patients based on age are dominated by age over 35 years (52%). Based on gestational age are dominated by gestational age less than 12 weeks (1st trimester) (68%). Based on the parity dominated by multiparous groups (39%). Based on previous history of abortion are dominated by patients who have never experienced abortion before (55%). And based on the type of abortion are dominated by patients who experience Imminent Abortion (61%).